Analysis of the effect of groundwater level on the seismic behavior of an unsaturated embankment on clayey ground. Issue 85 (June 2016) - Yoshikawa, Takahiro; Noda, Toshihiro; Kodaka, Takeshi; Takaine, Toshihiro
Abstract: Numerous river levees on clayey soil grounds were damaged by the 2011 off the Pacific coast of Tohoku Earthquake. In order to investigate such damage, the behavior of an unsaturated embankment on clayey ground was simulated during its construction, during an earthquake and after the earthquake. The simulation was carried out using a soil–water–air coupled finite deformation analysis code, with attention being focused on the effect of groundwater level. The results indicated that if the groundwater level is high, a saturated area (settlement-induced saturation area) is formed at the base of the embankment due to penetrative settlement during/after construction. In addition, the mean skeleton stress is low compared with the low groundwater level. As a consequence, in the embankment on ground with the high groundwater level, the co-seismic deformation is greater and the mean skeleton stress decreases sharply, particularly in the settlement-induced saturation area during the earthquake. It was also shown that after the earthquake, the groundwater level rises because water flows toward the unsaturated embankment from the settlement-induced saturation area and/or the saturated clayey ground. If the groundwater level is high, in particular, a phreatic line is formed temporarily within the embankment. Highlights: A soil–water–air coupled finite deformation analysis was used for the simulation. A saturated area is formed at the base of the embankment during construction. In the case of a higher groundwater level, the co-seismic deformation is larger. The groundwater level rises temporarily after the earthquake.